Aspirin Dose and Prevention of Coronary Abnormalities in Kawasaki Disease - Frédéric Dallaire; Zoe Fortier-Morissette; Samuel Blais; Anita Dhanrajani; Dania Basodan; Claudia Renaud; Mathew Mathew; Astrid M. De Souza; Audrey Dionne; Joël Blanchard; Harrison Saulnier; Kimberley Kaspy; et al. (2017)
Acetylsalicylic acid (ASA) is part of the recommended treatment of Kawasaki disease (KD). Controversies remain regarding the optimal dose of ASA to be used. We aimed to evaluate the noninferiority of ASA at an antiplatelet dose in acute KD in preventing coronary artery (CA) abnormalities.This is a multicenter, retrospective, nonrandomized cohort study including children 0 to 10 years of age with acute KD between 2004 and 2015 from 5 institutions, of which 2 routinely use low-dose ASA (3-5 mg/kg per day) and 3 use high-dose ASA (80 mg/kg per day). Outcomes were CA abnormalities defined as a CA diameter with a z score ≥2.5. We assessed the risk difference of CA abnormalities according to ASA dose. All subjects received ASA and intravenous immunoglobulin within 10 days of fever onset.There were 1213 subjects included, 848 in the high-dose and 365 in the low-dose ASA group. There was no difference in the risk of CA abnormalities in the low-dose compared with the high-dose ASA group (22.2% vs 20.5%). The risk difference adjusted for potential confounders was 0.3% (95% confidence interval [CI]: -4.5% to 5.0%). The adjusted risk difference for CA abnormalities persisting at the 6-week follow-up was -1.9% (95% CI: -5.3% to 1.5%). The 95% CI of the risk difference of CA abnormalities adjusted for confounders was within the prespecified 5% margin considered to be noninferior.In conjunction with intravenous immunoglobulin, low-dose ASA in acute KD is not inferior to high-dose ASA for reducing the risk of CA abnormalities.